2018
DOI: 10.1073/pnas.1720714115
|View full text |Cite
|
Sign up to set email alerts
|

Activated integrins identify functional antigen-specific CD8+T cells within minutes after antigen stimulation

Abstract: SignificanceAssessing antigen-specific T cells is crucial for our understanding of immune reactions against pathogens and tumors, and for evaluating immunotherapies in patients. Existing techniques to evaluate the functionality of T lymphocytes all rely on de novo expression of proteins, typically intracellular cytokines, and therefore require elaborated protocols and reagents. We have established a simple flow cytometry-based method to assess the functionality of CD8+ T cells by identifying immediate changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(57 citation statements)
references
References 31 publications
7
50
0
Order By: Relevance
“…Therefore, short stimulation times should be preferred; for instance, cytokines and rapid activation markers (e.g., CD154, CD137, CD69) typically require only 5–12 h of stimulation before their levels are measurable intracellularly, on cell surfaces or in culture supernatants, ensuring minimal manipulation . Furthermore, β2‐integrin activation on activated T cells occurs even within minutes .…”
Section: Biological Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, short stimulation times should be preferred; for instance, cytokines and rapid activation markers (e.g., CD154, CD137, CD69) typically require only 5–12 h of stimulation before their levels are measurable intracellularly, on cell surfaces or in culture supernatants, ensuring minimal manipulation . Furthermore, β2‐integrin activation on activated T cells occurs even within minutes .…”
Section: Biological Applicationsmentioning
confidence: 99%
“…A common drawback of these techniques is that they all rely on upregulation or de novo synthesis of the read‐out markers, e.g., activation markers or cytokines, and therefore, require at least several hours of stimulation. Recently, a new approach for rapid identification of activated CD8 + T cells has been introduced, based on immediate changes of surface integrins that occur within minutes following antigen stimulation . The authors made use of the fact that resting antigen‐experienced T cells express high levels of membrane‐bound β2‐integrins .…”
Section: Biological Applicationsmentioning
confidence: 99%
“…Antigen-speci c β 2 -integrin activation on CD8 + T cells can be visualized by either mICAM-1 or m24 Ab staining In our previous work, antigen-speci c CD8 + T cells were detected with mICAM-1 complexes (without EDTA) [5]. We therefore tested if staining of activated CD8 + T cells with m24 Ab would be comparable to that obtained with mICAM-1, and to which extent EDTA in uences detection.…”
Section: Resultsmentioning
confidence: 97%
“…We have previously shown that antigen-speci c CD8 + T cells are successfully detected by staining of activated β 2 -integrins with uorescent mICAM-1 [5]. We therefore investigated whether mICAM-1 binding could also be used as a marker for detection of antigen-speci c CD4 + T cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation